Odpowiedzi

Najlepsza Odpowiedź!
2010-01-07T14:33:42+01:00
X + y = 15
10%x + 4%y = 6% * 15

x = 15 - y
0,1x + 0,04y = 0,06 *15

x = 15 - y
0,1 *(15 - y) + 0,04y = 0,9

x = 15 - y
1,5 - 0,1y + 0,04y = 0,9

x = 15 - y
- 0,06y = - 0,6 /: (-0,06)

x = 15 - y
y = 10

x = 15 - 10
y = 10

x = 5
y = 10
  • Użytkownik Zadane
2010-01-07T14:38:31+01:00
|x+y=15
|0,1x+0,04y=0,06*15 /*(-10)

|x+y=15
+|-x-0,4y=-9
___________
0,6y=6
y=10

x+10=15
x=15-10
x=5

|x=5
|y=10
2010-01-07T14:41:29+01:00
X + y = 15
10%x + 4%y = 6% * 15

x=15-y
0,1x+0,04y=0,06*15

x=15-y
0,1(15-y)+0,04y=0,9

x=15-y
1,5-0,1y+0,04y=0,9

x=15-y
-0,06y=-0,6 /:(-0,06)

x=15-y
y=10

x=5

spr.
x + y = 15
10%x + 4%y = 6% * 15

5+10=15
10%*5+4%*10=6%*15
0,5+0,4=0,9
0,9=0,9